(untitled) (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2005)
The policy of Cuban Health and social values by the light of the studies on science, technology and society. The work proposes an argument that highlights the relationship science-technology-society and development, in the policy of health of Cuba. It is to deepen in some topics proposed in the book by Feinsilver "Curing the masses. The policy of Cuban Health in and abroad", that can be evaluated in a different way, allowing to discover political factors and inherent cultural condictions to the development of the Cuban activity in Health. The objective to find the specifities of the Cuban success in health with the help of the Science- technology- society approach. As a conclusion we can say Cuban policy on health is generating opportunities to stablish a dynamic alternative of the exploration of knowledge in health, nearer to the necessities and the contextual social values